Perspective on bank-client cooperation: A survey of selected commercial banks in Uganda - Nkuutu, Geofrey; Ntayi, Joseph M. (African Journal of Business Management, 2012)
The ineffective communication channels, mistrust and uncommitted tendencies between banks and its clients continue to exist as evidenced by the continuous increase in the number of dormant account holders. Customers’ switch from one bank to another and decline in customers’ profile has persisted thereby affecting Bank-client cooperation. The purpose of the paper is to examine the relationship between communication, trust, relationship commitment and Bank-Client cooperation among selected commercial banks in Uganda. To achieve this objective, data were collected through a survey using a structured questionnaire administered to the accounts relationship managers and their clients. A total of 170 usable responses were collected. Reliability and validity of the measurement model was conducted and correlation tests were carried out to examine the relationship between study variables. Empirical findings suggest that communication, relationship commitment and trust have significant positive effects on Bank-client cooperation. In other words, efforts to these constructs can result into improved Bank-client cooperation. Findings of this paper are expected to benefit commercial banks in designing a structural operating framework for effective communication, relationship commitment and trust in the banking industry.
Keywords: Communication; trust; relationship commitment; bank-client cooperation; commercial banks